Implementasi Bahasa Kawi sebagai Semboyan Institusi di Indonesia - Dewi Yunairi; Wasudewa Bhattacarya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The entry of Sanskrit into Indonesia was a language contact and cultural contact known as the bilateral relationship between the Indian and the Indonesian archipelago. At that time, the dominant archipelago was the ancient Javanese people. When Sanskrit entered, it was followed by literature in India, so that in the archipelago, it was known that literature originated from India. During the reign of the kingdom of Kediri, whose king Darmawangsa Teguh Anantawikrama Tunggadewa, as king issued a policy, namely by discussing Indian literature in Sanskrit into Old Javanese, so that the syncritism process in Old Javanese literature was carried out by using Sanskrit into the text. Then gave birth to acculturation so that the language known as Kawi language emerged. The theory used to dissect this problem is the theory of linguistic landscape and uses the method of literature study and the method of reading and taking notes. The results of this study are related to the use of Kawi language in state institutions today, because it can be interpreted by history because at that time Hindu kingdoms dominated the archipelago more and could even expand outside the archipelago. The use of Kawi language in the motto of State institutions is a spirit of dedication to society and the State. In addition, the implementation of Kawi language in the slogan of this state institution shows that Kawi language still has an important, noble and main position in the Republic of Indonesia.